Software Development for Smart Home Process Control (MCIT: Proceedings of International scientific and practical conference, 2019)
Smart home technology, an application of Internetof Things (IoT), provides households with e.g., comfort, controland convenience. The technology has been around for sometimes,but its prevalence is not yet widespread, and thus the potentialshave largely been underestimated. The purpose of this paper is todevelop a comprehensive model that can explain a largepercentage of variance in the intention to use smart hometechnology.
Keywords: Arduino; Internet of things; microcontroller; Smart home; client-server architecture; sensors